LEVEL OF SATISFACTION ON SERVICES QUALITY OF LRT SOUTH OF SUMATRA DURING THE CORONA PANDEMIC - Driaskoro Budi Sidharta; Siti Nurlaili Triwahyuni; Herdi Agem Priyono; Tegar Brilianza (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2022)
ABSTRACTThis study aims to determine the quality level of South Sumatra LRT services during the corona pandemic. The population of this study was 360 persons of South Sumatra LRT customers by accidental sampling method. This research was conducted by distributing 24 questions using a questionnaire. Evaluation of the level of desire and performance of the South Sumatra LRT manager is measured using a Likert scale. The result of the evaluation was analyzed using the Customer Satisfaction Index and servqual (gap analysis). The results showed that overall South Sumatra LRT customer was very satisfied, as indicated by CSI of 85,6%. However, all variables need to be improved because there is still a gap between customer desires and the performance of LRT Sumatra Selatan services. The level of service related to preventing the spread of the coronavirus needs to be prioritized.ABSTRAKPenelitian ini bertujuan untuk mengetahui tingkat kualitas pelayanan LRT Sumatra Selatan pada masa pandemi corona. Populasi penelitian ini adalah pelanggan LRT Sumatra Selatan sebanyak 360 orang dengan metode accidental sampling. Penelitian ini dilakukan dengan menyebarkan 24 pertanyaan menggunakan kuesioner. Penilaian tingkat keinginan dan kinerja pengelola LRT Sumatra Selatan diukur dengan menggunakan skala Likert. Hasil evaluasi dianalisis dengan menggunakan Customer Satisfaction Index dan servqual (gap analysis). Hasil penelitian menunjukkan bahwa secara keseluruhan pelanggan LRT Sumsel sangat puas yang ditunjukkan dengan CSI sebesar 85,6%. Namun semua variabel perlu diperbaiki karena masih terdapat gap antara keinginan pelanggan dengan kinerja pelayanan LRT Sumatra Selatan. Tingkat pelayanan terkait pencegahan penyebaran virus corona perlu diprioritaskan.